Travelling Inspectors and the Making of Europe: Education Policy Learning and the Case of the Scottish School Inspectorate - Sotiria Grek (Universidade de Lisboa, 2014)
The paper examines the case of education policy learning in Europe and argues that, contrary to dominant assumptions, education is a fruitful area for the analysis of Europeanising processes. More specifically, an examination of the case of the Scottish school inspectorate's 'European' exchanges is particularly useful in relation to the study of international policy communities, their formation and particular workings, as it signals a new level of 'political work' (Smith, 2009): that of exporting, internationalising and then importing afresh one's local/national knowledge, once it has successfully gone through the international 'test', and is therefore still relevant and future-proof (to the nation). This is exemplified well through the role of these actors who, rather than being Brussels-based Europeans, invariably assume European identity depending on its exchange value - as the paper shows, due to the current political situation in Scotland and the Scottish National Party (SNP) government's aspiration for independence, that exchange value for Scottish actors is high.